Ninety-three years of agricultural accounting studies in Scopus journals: a bibliometric analysis from 1923 to 2020 - Mohammed Umar, Ibrahim; Mustafa, Hasri; Wai, Yeng Lau; Sidek, Shafie (Emerald Publishing, 2021)
Purpose – Agricultural accounting is gaining ground across different disciplines, rendering it a significant research area. This study aims to assess agricultural accounting research for the past 93 years in terms of publication frequency, subject areas, topics that received the most attention among researchers, as well as the institutions that contribute to this subject area. Design/methodology/approach – This study employs a bibliometric analysis collected through the Scopus database. The sample included 3,612 documents. The analyzed variables include the number of publications per year, documents published, country, author affiliation, keywords and active institutions. Analyses include graphical network maps. Findings – The findings of this study reveal the importance of supportive institutions, human capabilities and international collaboration in aiding research and development. It provides an overview of agricultural accounting literature over the years and aid researchers in this research domain to explore more studies and develop better arguments. The results also indicate the continuing growth in the number of publications in recent years by authorship; country include the USA, China, the UK, Australia and Germany; institutes include Chinese Academy of Sciences, Wageningen University and Research Centre; and the subject areas include Environmental Science; Agriculture and Biology sciences; and Social Sciences. The most frequent keywords connecting to author’s area of research, as highlighted in Figure 5, include agriculture, accounting, water accounting, environmental accounting and cost analysis. Research limitations/implications – The study is based on the Scopus database, which has limited coverage. The keywords of the literature search were restricted to “agriculture and accounting” or“agricultural and accounting” and the research approach limited to quantitative perspective. Practical implications – The findings may benefit policymakers as well as academicians toward understanding the areas of interest in agricultural accounting. Originality/value – This study provides the potential areas within agricultural accounting literature in a broader scope that deserve multiple accounting practices to cover diverse agricultural activities such as cost accounting, financial reporting, managerial accounting, auditing, taxation and financial information systems. The study suggests developing countries promote innovative research on agricultural practice to meet global scientific and technological developments.